(3GdHQb GdjeGfj aj GdaJM GdYKeGfj (B/s - (3GdfgQhGdj, eMeO Hf CMeO Hf eMeO,s (3J(B. 988 (3g`(B.s; (3GdLGSQ, MeO,s 1328-1421 (3gLQjG(B.s ((3GdQjGV (B:s (3OGQ GdjeGeI ddHMK hGdJQLeI hGdfTQ,s, 1967)
(3JGQjN Gdjef aj GdbQf GdYGTQ GdgLQj, eY JhSY aj CNHGQ ZRhGJ GdLQGcSI hGdYKeGfjjf dPdc GdbWQ(B.s
Keywords: (3Gdjefs -- (3JGQjNs -- (3GdMce GdYKeGfj, (B1538-1840s